The Effectiveness of Governmental Policy Measures on Controlling the Spread of Covid-19: Empirical Evidence from Around the World - Yassin, Lobna Abdallah (AUC Knowledge Fountain, 2022)
The rapid spread of COVID-19 in China and the world dramatically affected the development in China and many countries worldwide. Different governments applied various policy measures to control the virus and prevent its spreading inside their countries. These policy measures combined with this global health crisis have serious consequences on the health system in different countries and the world economy. This thesis aims to quantitatively measure the effectiveness of the governmental policy measures that are taken during the risk management of the coronavirus across different countries on controlling the spread of the virus. Also, this thesis highlights the different policies implemented to control the COVID-19 virus in 48 countries which represent a quarter of the member countries in the United Nations. I chose 8 countries from each region that implemented different preventive policy measures to control the COVID-19 virus. This thesis provides empirical evidence for the effectiveness of each policy using quantitative analysis known as time serious analysis. To achieve this objective, we use both quantitative and qualitative data to evaluate the effectiveness of governmental policy measures to combat COVID-19 in different countries. This data was analysed using both descriptive analysis and regression analysis to correlate the various policy measures and their impacts on the spreading of the virus. R software was used to produce different graphs to show the descriptive analysis, while STATA software was used to show the quantitative analysis. This study used the random-effect model to analyze the quantitative panel data. The results show that lockdown, curfew, airport shutdown, banning public transportation, closing places of worships, compulsory quarantines for travelers, random community testing, the use of the modern health technology were effective in identifying and controlling the spread of COVID-19 virus. We prove that most of the governments’ implemented policies were effective in controlling the spread of the COVID-19 virus.